PENGARUH EARNING PER SHARE (EPS), RETURN ON EQUITY (ROE) DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM (Studi Empiris Pada Perusahaan Otomotif dan Komponen Periode 2013- 2016) - Siti Rosidah; Budi Wahono; Muhammad Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACTThis research aims to determine the influence of Earning Per Share (EPS), ReturnOn Equity (ROE) dan Debt To Equity Ratio (DER) to stock price either partially..This study was conducted on Automotive and Componentsn Company listed onBEI period 2013-2016. Data analysis method used is multiple regression test toshow the influence of independent variable to dependent variable, with classicalassumption test. From the results of this study shows that the Earning Per Share(EPS) have a significant influence on Stock Price. But Return On Equity (ROE)and Debt To Equity Ratio (DER) not significant to Stock Price.Keywords: Earning Per Share (EPS), Return On Equity (ROE), Debt To EquityRatio (DER) dan Stock Price.